Development of Interactive Learning Media on Light Vehicle Engine System Based on Classpoint to Improve Student Learning Achievement (A Study on Light Vehicle Engine System Components for Grade XI Students at SMK Negeri 3 Seluma) - Sofian Hadi; Johanes Sapri; Eko Risdianto (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
Background of study: The low academic achievement of students in understanding the elements of light vehicle engine systems, particularly in the subject of engine management systems (EMS) at SMK Negeri 3 Seluma, is caused by the lack of use of interactive learning media that are interesting and suited to the characteristics of the students. Therefore, there is a need to develop innovative and interactive learning media to improve student academic achievement. Aims and scope of paper: This research aims to develop ClassPoint-based interactive learning media  on engine management system (EMS) materials and test the feasibility and effectiveness of these media in improving student learning achievement. The scope of the research is focused on grade XI TKR students at SMK Negeri 3 Seluma on the competence of light vehicle engineering regarding the elements of the light vehicle engine system. Methods: The research method uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Results: The results of the study showed that the ClassPoint-based learning media  developed was declared very feasible based on the results of validation of material experts, media experts, and positive responses from teachers and students with  an overall media feasibility assessment of 92.87% with an average percentage of 92.87%. In addition, the results of the effectiveness test showed a significant increase in student learning achievement, which was evidenced by the comparison of pretest and posttest scores between the experimental class and the control class using the t test with the result t calculated = 2.730 > t table = 1.995 (N=69, α=0.05). Conclusion: The conclusion of this study is that ClassPoint-based interactive learning media is effective and feasible to be used as a learning tool in engine management system (EMS) materials to improve student learning achievement.